(untitled) (The Peerian Journal, 2024)
One of the most significant developments in the history of Uzbek literature is the emergence of fiction, encompassing a diverse range of genres such as science fiction, adventure, folklore, and mythological fiction. The incorporation of mythological, legendary and fairy-tale elements played a significant role in the development of Near and Middle Eastern literatures, as evidenced by works such as One Thousand and One Nights from the Arab East, Kalila and Dimna from India, Kabus-name from Iran, and Kerr-ogly from Turkic peoples.